Environmental assessment of landuse systems and water resources in the Tyumie river basin - Ayirebi, Godwin Kofi (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: This study advocates the application of integrated catchment principles as a model for the solution of the water scarcity and landuse problems of the Tyumic catchment basin in the Eastern Cape. The study identifies the sources of water, the distances travelled by users of waterand the perception of the community members about the water quality of the area. It also discusses the intensity of involvement of the communities in agricultural activities such as animal rearing and crop cultivation. The findings suggest that the lack of water in the area is due to inadequate planning and maintenance of water infrastructure. This has contributed to the departure of population to urban areas for alternative jobs. The intensity of agricultural practice was found to be very low. The study further reveals the paucity of water quantity that the rural areas use for their daily chores. Villagers are however much involved in the progress of water development projects and would be willing to pay a minimal amount for water provision in local areas if their efforts are required. A policy recommendation made from the study is that community related agriculture is necessary in the practice of a successful integrated catchment management policy as a form of redress to uplift the economic and social conditions of the basin.